Netnographic Study: Caring for Online Gender-Based Violence on Instagram @awaskbgo - Eranutrise, Desmie; Baiduri, Ratih; Rosramadhana (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study found the novelty of the fact that cases of gender-based violence does`t only occur in public spaces, but can also occur in cyberspace. Such as gender-based violence through media and internet networks which are referred to as cases of online gender-based violence. The purpose of this study is to contribute to knowledge of online gender-based violence prevention through Instagram social media. The type of research used is virtual ethnographic research or often called a netnographic study, which uses data collection techniques with in-depth interviews and participant observation. The results of the study show that Instagram social media is quite influential in providing education on online gender-based violence against women and Instagram social media users. Movements made in providing education can be through posts and opening discussions on live Instagram and in the comments column